CA-SLA: conversation analysis and second language acquisition - Pekarek Doehler, Simona (Chichester: Wiley-Blackwell Publishing, 2013)
Conversation analytic research on second language acquisition (CA-SLA) has emerged relatively late in the history of both CA and SLA. This is largely due to the historic development and the analytic focus of the two fields of research. On the one hand, ethnomethodological CA originated as a critical approach to society concerned with the local production of social order; it was not designed to address issues of learning or development. On the other hand, SLA research has traditionally been focused on the learner's internal cognitive processing of linguistic forms; it has paid only limited attention to the social-contextual dimensions of the learning of a second language (L2) (but see Hatch's, 1978, early statement). Yet, since the 1990s, the SLA scientific landscape has undergone a notable shift toward more socially, socioculturally, and sociocognitively oriented approaches, involving an increased awareness of the contingent, contextual, adaptive, and hence nonlinear nature of learning. CA research has played a major role in this development. In a much-quoted programmatic statement, Firth and Wagner (1997) have outlined the basic principles of what was later to become CA-SLA, calling for a “significantly enhanced awareness of the contextual and interactional dimensions of language use” (p. 286). Their argument has triggered a critical debate between cognitive and socially oriented SLA researchers (see Modern Language Journal, 1997, 81 [3], 2007, 91 [5]), and has provided major impulses for CLA-SLA research ever since.
Keywords: Language and social interaction; language in the classroom; second language acquisition; interactionist language studies